Politics and strategy : partisan ambition and American statecraft - Trubowitz, Peter (Princeton studies in international history and politics., 2011)
Why do some national leaders pursue ambitious grand strategies and adventuresome foreign policies while others do not? When do leaders boldly confront foreign threats and when are they less assertive? Politics and Strategy shows that grand strategies are Janus-faced: their formulation has as much to do with a leader's ability to govern at home as it does with maintaining the nation's security abroad. Drawing on the American political experience, Peter Trubowitz reveals how variations in domestic party politics and international power have led presidents from George Washington to Barack Obama.